Productivity and carbon sequestration potential of coconut-based cropping system as influenced by integrated nutrient management practices - Shinde, V.V.; Maheswarappa, H.P.; Ghavale, S.L.; Sumitha, S.; Wankhede, S.M.; Haldankar, P.M. (Journal of Plantation Crops, 2020)
A field experiment was carried out at Regional Coconut Research Station, Bhatye (DBSKKV, Dapoli), Maharashtra (India) during 2013-2018 to study the productivity and carbon sequestration potential as influenced by integrated nutrient management (INM) practices in coconut based cropping system. INM practices viz., T1- 75 per cent of RDF+25 per cent of N through organic recycling with vermicompost, T2- 50 per cent of RDF+50 per cent of N through organic recycling with vermicompost + vermiwash application + bio-fertilizer application + in situ green manuring (cowpea), T3- fully organic: 100 per cent N through organic recycling with vermicompost + vermiwash application + bio-fertilizer application + in situ green manuring (cowpea) and green leaf manuring + composted coir pith, husk incorporation and mulching with coconut leaves were imposed in coconut based cropping system involving nutmeg, cinnamon, banana and pineapple. For comparison, T4- control: monocrop of coconut with recommended NPK and organic manure was maintained. Four treatments were laid out in a block of 0.45 ha area each. Among the different INM practices, treatment T1 sequestered the highest amount of above ground (coconut + nutmeg) carbon stock (31.1 t ha-1) followed by T2 (30.3 t ha-1) and T3 (27.3 t ha-1). In contrast, the treatment T4 - coconut monocrop alone had sequestered 25.6 t ha-1. The below-ground soil carbon stock in the rhizosphere of different crops was the highest in the nutrient management under T3 followed by T2 and T1, whereas, it was the lowest in coconut monocrop. The productivity of the system was higher in the intercropping garden. The coconut nut yield (5-year average) was higher yield under T1 (147.2 nuts palm-1 year-1), followed by T2 (138.4 nuts palm-1 year-1) and T3 (123.6 nuts palm-1 year-1), whereas, monocrop had recorded a significantly lower number of nuts (97.2 nuts palm-1 year-1).